Letramento e construção identitária acadêmico - profissional em diários de leitura: formando professores para formar leitores - Ramos, Fabiana (2015)
This doctoral thesis aims to investigate how the genre reading journal, understood as an academic literacy event, can enhance academic professional identity of undergraduate students in initial teacher education. This qualitative study focuses on the Children‟s Literature course in the Pedagogy undergraduate program at the Federal University of Campina Grande (UFCG), and the corpus consists of journals produced by five participants during one semester, in 2013. Situated in the Applied Linguistic field, this piece of research is grounded in Cultural Studies (HALL, 2001, 2012), Bauman´s(2001, 2005) sociological perspective, New Literacy Studies (KLEIMAN 1995, 2007, 2008; BARTON & HAMILTON, 2000, among others), Sociodiscursive Interactionism (BRONCKART, 1999, 2006, 2008, BRONCKART & MACHADO, 2009), and the Work Sciences (CLOT, 1999[2006]). Based on the underlying assumptionthat identity construction is a sociodiscursive activity (SILVA & MATÊNCIO), and on the textual analysis model proposed by Sociodiscursive Interactionism (BRONCKART, op.cit), I will focus on the enunciative level of the reading journals, as well as on the thematization of the constitutive elements of teachers´ work (BRONCKART & MACHADO, op.cit), in light of SDI. The reading journal analysis revealed three identity categories: (i)) reader of children‟s books; (ii) undergraduate student in initial teacher education, and iii) teacher developing readers of children´s books. Such identities are (re)constructed in a network of voices in which the empirical authors of the journals shift to the past, present and future, reframing their experiences as school students, undergraduate students and beginning teachers, underscoring the appropriation of university discourses and the professional genre(CLOT& FAIT, 2000; FAÏTA, 2004), such as the official Brazilian guidelines and teacher education, as well as concepts and practices of the teachers´ collective. In sum, this study highlights the reading journal as an important toolfor teacher identity construction, enabling developmental mediation (BRONCKART, 2006) and enhancing socioprofessional identities of university students by means of enunciative positioning in the journals -as readers, as undergraduate students and as teachers developing readers.